Synergistic effects of resveratrol (free and inclusion complex) and sulfamethoxazole-trimetropim treatment on pathology, oxidant/antioxidant status and behavior of mice infected with Toxoplasma gondii - Bottari N.B. (2016)
© 2016 Elsevier Ltd.This study aimed to investigate the synergistic effects of resveratrol and sulfamethoxazole-trimethoprim (ST) on the treatment of mice experimentally infected by Toxoplasma gondii during the chronic phase of the disease considering infection, behavior, and oxidative/antioxidants profile aspects. For the study, 60 mice were initially divided into two groups: uninfected (n = 24) and infected by T. gondii (n = 36). These two groups were later subdivided into other groups and treated with resveratrol (free and inclusion complex containing resveratrol) alone and co-administered with ST: groups A to D were composed by healthy mice and groups E to J were consisted of animals infected by T. gondii (VEG strain). Treatments began 20 days post-infection for 10 consecutive days with oral doses of 0.5 mg kg-1 of ST (groups B and F), 100 mg kg-1 of free resveratrol (groups C and G) and inclusion complex of resveratrol (nanoparticles containing resveratrol) (groups D and H), and lastly an co-administration of both drugs (groups I and J). Behavioral tests (memory, anxiety and locomotion) were performed after treatment. Liver and brain fragments were collected to evaluate pathological changes, brain cysts counts, as well as oxidant and antioxidant levels. A reduction on the number of cysts in the brain of animals treated with both drugs combined was observed; there was also reduced number of lesions on both organs. This drug combined effect was also able to reduce oxidative and increase antioxidant levels in infected mice, which might be interpreted as a resveratrol protective effect. In addition, the combination of ST and resveratrol was able to prevent behavioral changes in infected mice. Therefore, the use of co-administration drugs enhances the therapeutic effect acting on a synergic way, reducing the oxidizing effects of the chemical treatment for toxoplasmosis. In addition, resveratrol in inclusion complex when co-administered with ST showed an improved therapeutic effect of ST reducing oxidative damage, liver damage and the number of cysts in the brain of T. gondii infected mice.